2021
DOI: 10.1016/j.radi.2021.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Radiographers and COVID-19 pneumonia: Diagnostic performance using CO-RADS

Abstract: Introduction: A more structured role of radiographers is advisable to speed up the management of patients with suspected COVID-19. The purpose of our study was to evaluate the diagnostic performance of radiographers in the detection of COVID-19 pneumonia on chest CT using CO-RADS descriptors. Methods: CT images of patients who underwent RT-PCR and chest CT due to COVID-19 suspicion between March and July 2020 were analysed retrospectively. Six readers, including two radiologists, two highly experienced radiogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 18 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…The results of a sensitivity analysis for 28 studies, including more than 50 subjects among both COVID-19 cases and non-COVID-19 cases, each, were similar to those of the primary analysis [ 9 , 20 24 , 26 28 , 30 , 33 38 , 41 , 45 48 , 50 52 , 54 57 ] (Additional file 1 : Fig. 4).…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…The results of a sensitivity analysis for 28 studies, including more than 50 subjects among both COVID-19 cases and non-COVID-19 cases, each, were similar to those of the primary analysis [ 9 , 20 24 , 26 28 , 30 , 33 38 , 41 , 45 48 , 50 52 , 54 57 ] (Additional file 1 : Fig. 4).…”
Section: Resultsmentioning
confidence: 53%
“…There were 18 studies from developing countries (4 studies from lower-middle-income and 14 studies from upper-middle-income countries) [ 18 , 19 , 22 , 23 , 30 – 32 , 35 , 37 , 38 , 43 45 , 47 , 48 , 50 , 51 , 58 ] and 24 studies from developed countries (high income) [ 9 , 20 , 21 , 24 29 , 33 , 34 , 36 , 39 42 , 46 , 49 , 52 57 ]. The included studies were predominantly from Europe (24 studies) [ 9 , 20 , 21 , 23 27 , 29 , 31 , 32 , 34 , 35 , 37 , 38 , 41 , 42 , 47 49 , 52 , 55 57 ], followed by the Americas (10 studies), Asia (seven studies), and Africa (one study). Nineteen studies for assessing the interobserver agreement are summarized in Additional file 1 : Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…CO-RADS was able to distinguish between patients with positive PCR results from those with negative PCR results with an average AUC of 0.91 (95% CI: 0.85, 0.97) [27]. A recent study [28] confirmed that this score is a useful tool allowing radiographers to recognise the classic appearance of COVID-19 on CT in a way comparable to expert radiologists.…”
Section: The Diagnosis Of Covid-19 Pneumonia With Ldctmentioning
confidence: 87%
“…All assays were performed according to the instructions of the manufacturer. Low-dose CT or CT-angiography scans were assessed using CO-RADS, a published and validated score for suspicion of pulmonary involvement, with a score of 1, 2 or 3 (very low, low and equivocal suspicion, respectively) considered negative, and a score of 4 or 5 (high and very high suspicion, respectively) rated positive (21)(22)(23)(24)(25).…”
Section: Methodsmentioning
confidence: 99%